Migrants in liminal time and space: an exploration of the experiences of highly skilled Indian bachelors in Amsterdam. Issue 16 (10th December 2017) - Kirk, Kate; Bal, Ellen; Janssen, Sarah Renee
ABSTRACT: This paper sheds light on the relationship between individual agency, transnational social relations, geographic place, and cultural constructions of life phase and gender among highly skilled Indian migrants to the Netherlands. Amsterdam is attracting an increasing number of Indian migrants who work primarily in the fields of information technology, engineering and business management. The nature of this highly skilled work requires mobile, flexible workers, and therefore mainly attracts single men between 25 and 34. Their migrant experiences and choices are marked by a 'performance of liminality': migration is part of a coming of age ritual that both structures their lives and is structured by circumstances and agency. The experience of bachelors in particular can be understood as a 'double liminality' in that it is both temporary and spatial. Many of our bachelor informants felt they were 'betwixt and between' the socio-cultural expectations they grew up with and what they perceive to be Dutch or Western culture, and between those that pertain to childhood and to adulthood. They live on a metaphorical threshold, shaped by their masculine ideals, beliefs about 'Indian culture', their expected life trajectories, and their experiences in and expectations of the Netherlands and the city of Amsterdam.